Total Phenolic Contents and Antioxidant Activities of Different Extracts and Fractions from the Aerial Parts of Artemisia biennis Willd - Hatami, Tayyebe (Shaheed Beheshti University of Medical Sciences, 2014)
Total phenolic contents (TPC) of five different extracts (petroleum ether, dichloromethane, ethyl acetate, ethanol and ethanol-water) of Artemisia biennis Willd were measured in this work. The antioxidant activity was investigated by three different methods: β-carotene bleaching (BCB) test, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method and ferrous ion chelating (FIC) assay. Among all the extracts analyzed, the hydroethanolic extract exhibited a significantly higher phenolic content and antioxidant activity than other samples. Vacuum liquid chromatography of this extract yielded seven fractions (A to G) which were subjected to all aforementioned experiments. The highest total phenolic content and free radical scavenging activites were present in the same sample (Fraction D) but the only statistically significant correlation between TPC and EC(50) values was observed for BCB.